Modelling the live-electronics in electroacoustic music using particle systems - Perrotta, Andre V.; Menezes, Flo [UNESP]; Martins, Luis Gustavo (My University, 2014)
Developing the live-electronics for a contemporary electroacoustic piece is a complex process that normally involves the transfer of artistic and aesthetic concepts between the composer and the musical assistant. Translating in technical terms the musical, artistic and aesthetic concepts by means of algorithms and mathematical parameters is seldom an easy and straightforward task. The use of a particle system to describe the dynamics and characteristics of compositional parameters can reveal an effective way for achieving a significant relationship between compositional aspects and their technical implementation. This paper describes a method for creating and modelling a particle system based on compositional parameters and how to map those parameters into digital audio processes. An implementation of this method is described, as well as the use of such a method for the development of the work O Farfalhar das Folhas (The rustling of leaves) (2010), for one flutist, one clarinetist, violin, violoncello, piano and live-electronics, by Flo Menezes. Copyright: